Implementasi Program Bantuan Langsung Tunai (BLT) Dana Desa di Kecamatan Modayag Barat Kabupaten Bolaang Mongondow Timur - Mamonto, Armitha; Aneta, Yanti; Nani, Yacob Noho (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to identify and explain the implementation of the Village Fund Direct Cash Assistance (BLT) Program in Modayag Barat Subdistrict, East Bolaang Mongondow Regency. It is viewed from the following aspects: (1) communication, (2) resources, (3) disposition of the implementers, and (4) bureaucratic structure. This research uses a qualitative approach with descriptive research methods and qualitative analysis. Data collection techniques used in this study include observation, interviews, and documentation. The results of the study indicate that the implementation of the Village Fund BLT Program in Modayag Barat Subdistrict, East Bolaang Mongondow Regency, has been carried out, although there are still some obstacles in its implementation that show inefficiencies in the process. In terms of communication, the village government has conducted special village meetings, determined prospective beneficiaries, and conducted public outreach. However, communication between the village government and the regional government remains ineffective, which affects the smoothness of the program. The resources involved in the implementation of the program include village heads, village officials, the Village Consultative Body (BPD), and BLT facilitators at the subdistrict level. The amount of aid distributed is IDR 300,000 per beneficiary household (KPM), adjusted according to the Village Fund budget of each region. In terms of implementers’ disposition, no significant obstacles were found since all processes were carried out by the village apparatus, supported by the BPD and BLT facilitators. The village government is fully responsible for all stages of implementation, from data verification and beneficiary determination to fund disbursement. The bureaucratic structure of BLT implementation refers to mechanisms established by the village head, consisting of a series of processes starting from the determination of beneficiary criteria through special village meetings, followed by official determination meetings, preparation of meeting minutes and attendance lists, and public dissemination. The final stage of this program’s implementation is the cash distribution of aid, delivered directly to beneficiaries based on the pre-established list.